Parkgoers go to the virtual park: a classification framework, systematic review, and future tourism research agenda - Aniesa Samira Bafadhal; Faiz Izwan Anuar; Mohd Hafiz Hanafiah (Cogent Social Sciences)
Introduction Virtual reality (VR) technology has revolutionized park experiences, offering high-tech, low-touch solutions that cater to parkgoers throughout the COVID-19 pandemic and beyond. Despite its potential, research on virtual parks remains nascent, necessitating further exploration to establish a robust field within tourism and leisure studies.Methods This study employed ATLAS.ti version 23 to conduct a Systematic Literature Review (SLR) focused on developing a Human-Computer Interaction (HCI) classification framework for virtual parks following the established guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020. The review aimed to synthesize existing knowledge and identify gaps in the current research landscape.Results The SLR identified 72 relevant studies that aligned with the proposed HCI classification framework. Findings underscored the diversity and potential impact of virtual parks across various types, including virtual amusement parks, archaeological parks, geoparks, national parks, natural parks, theme parks, underwater parks, and urban parks. The framework comprehensively covered current issues and future developments in virtual park research, providing a foundation for future studies.Discussion This is the first study that represents a pioneering effort in developing a virtual theme park framework and reviewing virtual parks within the tourism context. The results underscore VR’s role in enhancing traditional park services, supporting tourism management performance, and improving parkgoers’ well-being. This pioneering effort also contributes to understanding the implications of virtual parks in broader societal advancements related to the tourism industry.